Pola Kekuasaan Pendisiplinan dalam Membina Perilaku Peserta Didik di SMA Negeri Olahraga Sriwijaya - Lamtarida Deasy Marice; Ridhah Taqwa (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2020)
The research was conducted at Sriwijaya Sports State High School, a special school for students who have talent in the field of sports. The aim is to know the pattern of discipline and the form of disciplinary techniques applied in fostering student behavior. The method used is descriptive qualitative with a case study approach that explores important information about the pattern of application and the form of disciplinary techniques. The data analysis is done by processing and preparing data, reflecting on meaning, processing information, data coding, and making narrative writings. The results of the study show that disciplinary patterns are applied through two mechanisms: first is through supervision (panapticon). This form of supervision takes the form of a point system that has the power to oversee the behavior of students. Other forms of supervision are raids on behavior that violates school rules. Second is the normalization, which is done by applying and enforcing punishment and reward. Disciplinary techniques that are carried out including the use of democratic discipline, permissive discipline, and the application of punishment that is educational in value, but does not lead to a form of violence.